O19 Secukinumab-related gastrointestinal safety in PsA and AS. (20th April 2020) - Onac, Ioana A; Tacu, Cristina; Clarke, Benjamin D; Lloyd, Mark; Hajela, Vijey; Batty, Thomas; Thoroughgood, Jamie; Smith, Sandra; Irvine, Hannah; Hill, Diane; Baxter, Grace; Horwood, Natalie; et al.
Abstract: Background: Secukinumab is a selective interleukin-17a inhibitor (anti-IL17) and an effective treatment option for psoriatic arthritis (PsA) and ankylosing spondylitis (AS). Phase III study safety data indicate a possible risk of inflammatory bowel disease (IBD), a link which is biologically plausible as IL-17 is known to influence intestinal immunopathology. Real world data for secukinumab gastrointestinal safety are limited. We set out to describe the post-licensing experience of secukinumab in routine care, evaluating both baseline evaluation of pre-existing IBD as well as incident gastrointestinal adverse effects. Methods: We undertook a retrospective cohort study. Ten centres from the South East of England participated. All records for patients commencing secukinumab at each centre between 2016-2019 were reviewed. A fully anonymised data collection form was used to collate patient information. Questions sought to answer whether IBD screening had occurred prior to secukinumab initiation. All gastrointestinal adverse events were reviewed. IBD-related adverse events after initiation were defined as: definite (biopsy confirmed, objective inflammation from biomarkers, clear temporal association, improvement on drug withdrawal), probable (as per definite, but without biopsy confirmation) or possible (gastrointestinal symptoms not fulfilling definite or probable criteria). Results: Data for 306 patients were available: 124 (40.5%) with AS and 182 (59.5%) with PsA. 106 (34.6%) of patients had documented assessment for IBD prior to initiation; 7 of which already had pre-existing diagnoses of IBD. 24 (7.8%) patients experienced gastrointestinal related adverse events after starting secukinumab; 18 of which were formally investigated for bowel disease due to symptoms. Amongst patients who developed gastrointestinal symptoms, 4 (1.3%) had definite, 7 (2.3%) probable and 13 (4.2%) possible IBD. Out of the 4 with definite IBD; all were AS patients, all stopped secukinumab, three had pre-existing IBD and one (0.3%) case of de-novo IBD required surgical management for an inflammatory perianal abscess. All 7 patients with probable IBD had symptom resolution on withdrawal of secukinumab. Of these, 4/7 were PsA and 3/7 were AS. For the 13 patients that fulfilled possible IBD criteria, symptoms resolved without intervention and continued secukinumab treatment. Conclusion: Absolute rates of new IBD in patients starting secukinumab are low. In addition, a majority of patients developing new gastrointestinal symptoms did not develop objective evidence of IBD or stop therapy. However, our experience suggests that in people with pre-existing IBD the risk is much higher. Only one-third of patients had documented evidence of screening for IBD at baseline. Given that only one patient developed de-novo IBD in the cohort, our experience would not support the practice of pre-screening for IBD prior to starting anti-IL17 therapy. Further research to evaluate this would be wise to focus specifically on the characteristics of AS patients, stratifying IBD risk prior to anti-IL17 initiation. Disclosures: I.A. Onac: Other; Education support to attend conference from Abbvie. C. Tacu: Honoraria; Novartis Pharmaceutical UK - Speaker Fee. Other; education support- course - Novartis. B.D. Clarke: None. M. Lloyd: Other; departmental support from Novartis. V. Hajela: None. T. Batty: None. J. Thoroughgood: None. S. Smith: None. H. Irvine: None. D. Hill: None. G. Baxter: None. N. Horwood: Other; attend conferences from Lilly and Abbvie. S. Mahendrakar: Other; Education support to attend conferences from Lilly. R. Rajak: Honoraria; Honoraria for speaker: Eli Lilly, Amgen, Internis, Roche, UCB, Abbvie. Honoraria for chairing: Roche, Novartis, Eli Lilly, UCB. S. Griffith: Other; None declared. P. Kiely: Honoraria; Abbvie, BMS, Gilead, Lilly, Novartis, Sanofi. Member of speakers' bureau; Abbvie, BMS, Lilly, Novartis, Sanofi. J.B. Galloway: Honoraria; Speaker fees, travel support and grants from Lilly, Abbvie, BMS, Celgene, Janssen, Pfizer, UCB, Sanofi.